Joint torques estimation in human gait based on Gaussian process - Yang, Jiantao; Wang, Zekai; Sun, Tairen (Technology and health care, 2023)
Human gait involves activities in nervous and musculoskeletal dynamics to modulate joint torques with time continuously for adapting to varieties of walking conditions. The goal of this paper is to estimate the joint torques of lower limbs in human gait based on Gaussian process. The potential uses of this study include optimization of exoskeleton assistance, control of the active prostheses, and modulating the joint torque for human-like robots. To achieve this, Gaussian process (GP) based data fusion algorithm is established with joint angles as the inputs. The statistic nature of the proposed model can explore the correlations between joint angles and joint torques, and enable accurate joint-torque estimations. Experiments were conducted for 5 subjects at three walking speed (0.8 m/s, 1.2 m/s, 1.6 m/s). The results show that it is possible to estimate the joint torques at different scenarios.